Analysis of 2024 General Election Digitalization System as An Effort to Improve The Quality of Democracy in Indonesia - Dimyati Huda; Agus Edi Winarto; Lestariningsih Lestariningsih (Journal of Development Research, 2023)
In carrying out the stages of holding the 2024 General Election, KPU uses digital application systems. The purpose of this research is to describe and analyze the strengths and weaknesses of implementing the digital application systems. Researchers studied primary data of general election laws and KPU regulations, and secondary data of some books and relevant electoral journal articles. They also explored empirical data from the Commissioners of KPU of Kediri Regency. In analyzing the data, researchers used Miles and Hubberman's theory. The results of this study show that the eight digital application systems used by KPU, namely: Sipol, Sidalih, Silon, Sidapil, Sidakam, Sirekap, Silog, and Siakba make a very large contribution to every stage of the 2024 General Election so that they become more effective, efficient, transparent, accurate, and up to date. Common weaknesses occur when data transmission is carried out simultaneously at one time, it has possibility problem for data traffic because the size of the server may not sufficient; second, the internet network is not evenly distributed throughout Indonesia; and third; not all of the human resources for general election organizers at the lower levels are capable of operating the digital system properly. To improve the quality and to get the maximum results of election, general election organizers need to anticipate closing the gaps in digital application system deficiencies in holding the 2024 general election in Indonesia.